The Cultural and Historical Trail Map of Peranakan Heritage in the Andaman Provincial Cluster in Thailand - Thippiroon Poomduang (Jurnal Komunikasi Pembangunan, 2021)
This study explored the trace of Peranakan heritage in the Andaman provincial cluster and presented the Cultural and Historical Trail Map of Peranakan heritage in Andaman provincial cluster. The concept of development communication objectives was used to create a research framework. Research results in the "complement" phase showed 117 traces of Peranakan heritage in the Andaman provincial cluster. As for the "facilitate" phase, 83 sites were qualified. An analysis of the relationship of qualified sites with Peranakan culture revealed five significant connections between each location and culture: 1) Peranakan ancestral monument, 2) Peranakan shrine, 3) Sino-European architectural building, 4) Peranakan residential areas, and 5) Peranakan cultural and historical learning center. Upon completion of the last phase, "extend," 6 tourist maps were created to display 8 cultural sites in Ranong province, 15 sites in Phang Nga province, 33 sites in Phuket province, 8 sites in Krabi province, 14 sites in Trang province, and 4 sites in Satun province, respectively. This study, thus, has produced a visual map in each province which is a catalytic communication tool to promote tourism development at the regional level and national level.